Diagnostic Accuracy and Field for Improvement of Frameless Stereotactic Brain Biopsy: A Focus on Nondiagnostic Cases - He, Zhexi; Zhu, Cannon Xian Lun; Chan, Danny Tat Ming; Cheung, Tom Chi Yan; Ng, Ho-Keung; Mok, Vincent Chung Tong; Poon, Wai Sang (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background The diagnostic accuracy of frameless stereotactic brain biopsy has been reported, but there is limited literature focusing on the reasons for nondiagnostic cases. In this study, we evaluate the diagnostic accuracy of frameless stereotactic brain biopsy, compare it with the current international standard, and review the field for improvement.Methods This is a retrospective analysis of consecutive, prospectively collected frameless stereotactic brain biopsies from 2007 to 2020. We evaluated the diagnostic accuracy of the frameless stereotactic brain biopsies using defined criteria. The biopsy result was classified as conclusive, inconclusive, or negative, based on the pathologic, radiologic, and clinical diagnosis concordance. For inconclusive or negative results, we further evaluated the preoperative planning and postoperative imaging to review the errors. A literature review for the diagnostic accuracy of frameless stereotactic biopsy was performed for the validity of our results.Results There were 106 patients with 109 biopsies performed from 2007 to 2020. The conclusive diagnosis was reached in 103 (94.5%) procedures. An inconclusive diagnosis was noted in four (3.7%) procedures and the biopsy was negative in two (1.9%) procedures. Symptomatic hemorrhage occurred in one patient (0.9%). There was no mortality in our series. Registration error (RE) and inaccurate targeting occurred in three trigonal lesions (2.8%), sampling of the nonrepresentative part of the lesion occurred in two cases (1.8%), and one biopsy (0.9%) for lymphoma was negative due to steroid treatment. The literature review suggested that our diagnostic accuracy was comparable with the published literature.Conclusion The frameless stereotactic biopsy is a safe procedure with high diagnostic accuracy only if meticulous preoperative planning and careful intraoperative registration is performed. The common pitfalls precluding a conclusive diagnosis are RE and biopsies at nonrepresentative sites.
Keywords: frameless stereotaxy; histology; image-guided surgery; intracranial; neuronavigation